Validation of Colchicine Assay Method for Therapeutic Drug Monitoring in Human Plasma - Fadime Canbolat (Journal of Advanced Research in Natural and Applied Sciences)
Colchicine (COL) reduces the frequency of attacks in Familial Mediterranean Fever (FMF) patients and is effective in preventing and arresting renal amyloidosis in most patients. COL has a narrow therapeutic window. The blood concentration to achieve therapeutic effects can be determined by Therapeutic Drug Monitoring (TDM). However, the use of selective and sensitive analytical methods is necessary for achieving success with TDM. The purpose of this study is to develop and validate a new method for quantitative assay of COL in human plasma samples by liquid chromatograph- tandem mass spectrometry (LC-MS/MS). In our study, to 1ml plasma sample, 0.25 ml internal standard solution was added. The solution was extracted by liquid-liquid extraction (LLE). The method was validated according to the European Medicines Agency (EMEA). The total run time was 8 min in LC-MS/MS. The method has been validated over the 0.25 - 8.0 ng/mL calibration range for COL. It was seen that the method has been validated since the results of the analysis meet the EMEA criteria. In our study, COL plasma levels were found to be approximately 1.097±0.42 ng/ml in 40 FMF patients using an oral dose of 1.5-2 mg/day. A validated, rapid, simple, cost-effective, and sensitive LC-MS/MS method was developed and optimized for quantitation of COL in plasma. It has been thought that pharmacokinetic studies of COL in plasma can be performed easily using this validated method